Fenomena Kopi Kekinian di Era 4.0 Ditinjau dari Marketing 4.0 dan Teori Uses and Effect - Alfirahmi Alfirahmi (LUGAS Jurnal Komunikasi, 2019)
The Luckin coffee phenomenon in China, and the development of information and communication technology have triggered the development of contemporary coffee in Indonesia. The contemporary coffee that combines coffee with milk, coupled with putting forward the concept of an instagrammable, comfortable outlet, is the main attraction for the millennials. This study uses the uses and effect theory, and the marketing concept 4.0. The method used in this research is qualitative method. The results obtained from this study are that the marketing method carried out by coffee now promotes marketing 4.0, by integrating marketing channels, payment channels and logistics channels through online and offline systems. If coffee was once known as drinks for elder people, with the development of technology, many marketers are utilizing the interaction of internet users to market their products. Another impact of technological development is the emergence of convergence. Convergence in this case not only on the impact of media on life, but convergence has given rise to a new culture. This can be seen from the number of young people who began to use coffee as part of a culture of friendship and style in social activities.